History of Customary Law - Naufal Thariq Eka Putra; Elza Qorina Pangestika (Yayasan Adra Karima Hubbi, 2024)
Background. This article discusses the history of customary law, emphasizing its role in shaping community behavior. Human beings, from birth, have an instinct to understand the phenomena in social life, which form customs and manners. Purpose. Customs, including customary law, reflect the deposits of morality in society. Method. This study includes historical analysis and highlights the influence of Hinduism in the Hindu Age as well as the influence of Malaio Polynesia in other areas. Results. Customary law, with specificities such as its religio magical/religious aspects, is recognized as the result of acculturation between the customary rules of the Pre-Hindu era and Hindu, Islamic and Christian cultures. This article provides a brief understanding of the role of customary law in the historical context and discusses its influence on community life. The social and cultural implications of the continuation of adat law are also discussed in the context of contemporary society. Conclusion. This study provides a concise view of the historical dynamics of customary law, enhancing our understanding of the relationship between custom, historicity and social development.